Toxic Effects of Polychlorinated Biphenyl Congeners and Aroclors on Embryonic Growth and Development. (7th December 2020) - Singleman, Corinna; Zimmerman, Alison; Harrison, Elise; Roy, Nirmal K.; Wirgin, Isaac; Holtzman, Nathalia G.
Abstract: Polychlorinated biphenyls (PCBs) cause significant health and reproductive problems in many vertebrates. Exposure during embryogenesis likely leads to defects in organ development, compromising survival and growth through adulthood. The present study identifies the impact of PCBs on the embryonic development of key organs and resulting consequences on survival and growth. Zebrafish embryos were treated with individual PCB congeners (126 or 104) or one of 4 Aroclor mixtures (1016, 1242, 1254, or 1260) and analyzed for changes in gross embryonic morphology. Specific organs were assessed for defects during embryonic development, using a variety of transgenic zebrafish to improve organ visualization. Resulting larvae were grown to adulthood while survival and growth were assayed. Embryonic gross development on PCB treatment was abnormal, with defects presenting in a concentration‐dependent manner in the liver, pancreas, heart, and blood vessel organization. Polychlorinated biphenyl 126 treatment resulted in the most consistently severe and fatal phenotypes, whereas treatments with PCB 104 and Aroclors resulted in a range of more subtle organ defects. Survival of fish was highly variable although the growth rates of surviving fish were relatively normal, suggesting that maturing PCB‐treated fish that survive develop compensatory strategies needed to reach adulthood. Life span analyses of fish from embryogenesis through adulthood, as in the present study, are scarce but important for the field because they help identify foci for further studies. Environ Toxicol Chem 2021;40:187–201. © 2020 SETAC